A SCALE DEVELOPMENT ABOUT INFORMATION SECURITY AWARENESS OF SMES AGAINST CYBER RISKS: SAMPLE OF GAZIANTEP - ÇATUK, Cüneyt; YURTSEVER, Gülçimen (Atlas Journal, 2018)
After the advantages provided by the globalizing world and Internet technology, the Small and Medium Enterprises(SMEs) have become global companies from being regional companies. In addition to this advantage provided by the Internet and globalization, it also caused some risks for SMEs. For this reason, this study was conducted to develop a scale to measure the awareness of information security of SMEs. Content / Scope validity, criterion / related validity and construct validity of this scale have been proven. Exploratory factor analysis and confirmatory factor analysis were utilized for the construct validity, and Cronbach’s alpha coefficient was used for internal consistency reliability. There are 37 items on the scale. The data were obtained from the answers of 800 SMEs employees working in different sectors in Gaziantep to the questionnaire survey. According to the results of the research, this scale has four sub dimensions. Four sub-dimensions explain 67.33% of the total variance. The importance of the study constucted a new, valid and reliable scale to measure the perception of information security awareness in firms where SMEs employees are working. The result of this study may help to develop a better understanding of where SMEs need to focus information security concerns.